Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4103/1596-3519.76578
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria among adult sickle cell anemia patients in Nigeria

Abstract: Proteinuria which is a marker of renal insufficiency is common among adult SCA patients, and routine screening for proteinuria may help detect those at increased risk of renal disease. CKD prevalence is high among SCA patients with significant proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
4
18
1
Order By: Relevance
“…Twenty percent of the HbSS cohort had proteinuria, which is similar to the 22.3% reported by Iwalokun et al [21] and the 28% reported by Abdu et al [22]. To the contrary, Bolarinwa et al [23] reported a higher prevalence of proteinuria (50%) in their HbSS cohort; a probable explanation for this high level of proteinuria could be the inclusion of individuals with both microalbuminuria and macroalbuminuria in their study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Twenty percent of the HbSS cohort had proteinuria, which is similar to the 22.3% reported by Iwalokun et al [21] and the 28% reported by Abdu et al [22]. To the contrary, Bolarinwa et al [23] reported a higher prevalence of proteinuria (50%) in their HbSS cohort; a probable explanation for this high level of proteinuria could be the inclusion of individuals with both microalbuminuria and macroalbuminuria in their study.…”
Section: Discussionsupporting
confidence: 81%
“…Stage 3 has been reported to represent a critical point in the spectrum of CKD, as it marks the beginning of established kidney disease according to the K/DOQI classification [15]. An earlier report by Abdu et al [22] from Kano, north central Nigeria, noted that as much as 50% of SCD patients with proteinuria had CKD. This finding further underscores the importance of proteinuria in the assessment of renal status in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study significant microalbuminuria, which is an early predictor of glomerular lesion, was observed in 27% of cases, which is lower than the described in previous studies [18,19,20,21,22,23,24]. This difference could be attributable to differences in genetics, includuing different haplotypes.…”
Section: Discussioncontrasting
confidence: 55%
“…A Previous study reported the relationship between albuminuria and inflammation, and hemolysis [17]. This report has been confirmed by our results, albuminuria was positively correlated with leukocytes count and LDH level.…”
Section: Discussionsupporting
confidence: 91%